Being someone or doing something: How students in municipal adult education view their future vocation - Tobias Lasse Karlsson (Nordic Journal of Vocational Education and Training, 2022)
Being an adult, deciding what to do with your life, and trying to understand the consequences of educational choices can be difficult. Vocational education and training (VET) programmes within the Swedish municipal adult education (MAE) offer an opportunity to learn a vocation, and last 6–18 months. This study aims to explore how adult VET students perceive desirable vocational habitus and is based on 18 interviews comparing students from two vocational MAE programmes in assistant nursing and floor laying. Semi-structured interviews were conducted at the beginning of the students’ training and data were analysed using inductive thematic analysis. The results show that choosing a VET programme is a process of choosing what you want to do for work but also who you want to be. However, whether or not students see themselves as suitable is contrasted between how they perceive their future vocation and what the vocational community expects from them, which in turn affects their learning process and development of a vocational identity. Noticing the discrepancies between students’ perceptions and vocational expectations can both reduce the risk of losing students during training and reduces the risk of reproducing unequal ideals.